A Spatial Theory of Trade - Rossi-Hansberg, Esteban (American Economic Review, 2005)
The equilibrium relationship between trade and the spatial distribution of economic activity is fundamental to the analysis of national and regional trade patterns, as well as to the effect of trade frictions. We study this relationship using a trade model with a continuum of regions, transport costs, and agglomeration effects caused by production externalities. We analyze the equilibrium specialization and trade patterns for different levels of transport costs and externality parameters. Understanding trade via the distribution of economic activity in space naturally rationalizes the evidence on border effects and the “gravity equation.”